HUBUNGAN WAKTU TUNGGU DENGAN KEPUASAN PASIEN DI INSTALASI RAWAT JALAN - Miranda, Elfa Dhela; Mayasari, Ayu Dewi; Hastuti, Hastuti; Harun, Lukman (Ensiklopedia of Journal, 2025)
Abstract: Patient satisfaction is one of the important indicators that reflect the results or outcomes of health services provided by health facilities. One aspect that can reduce patient satisfaction is waiting time that is too long in health services. The purpose of the study was to determine the relationship between waiting time and patient satisfaction in the outpatient installation. The research design used in this study was cross sectional. The research was conducted at the outpatient installation of the Banjarnegara Islamic Hospital. The research was conducted in September 2024. The study population was all patients who came to utilize services at the Banjarnegara Islamic Hospital outpatient installation. The research sample amounted to 92 respondents. The sampling technique used in this study was purposive sampling. Data analysis was carried out univariate and bivariate. The results of the study showed a relationship between waiting time (p value: 0.000) on patient satisfaction. It is recommended for the hospital to routinely observe services in order to maintain existing strengths and always improve service quality.Keywords: Satisfaction, Hospital, Waiting Time.